Retention of Zn, Fe and phytic acid in parboiled biofortified and non-biofortified rice - Taleon, Victor; Gallego, Sonia; Orozco, Juan Camilo; Grenier, Cecile (Elsevier, 2020)
Biofortified rice with high Zn concentration could reduce Zn deficiency in South Asia. This population frequently parboils rice. True retention (TR) of Zn, Fe and phytic acid after parboiling and milling was evaluated in biofortified and non-biofortified rice. TR in milled non-parboiled rice was 63.8–89.6% for Zn, 21.1–44.5% for Fe and 16.4–40.3% for phytic acid, whereas in milled parboiled rice TR was 49.8–72.2% for Zn, 23.4–36.7% for Fe and 22.0–33.3% for phytic acid. Milled parboiled rice resulted in lower Zn TR compared to milled non-parboiled. These results suggest that Zn moves from the inner endosperm towards the outer layers during parboiling, regardless of initial Zn concentration, consequently, once milled, the potential impact of Zn intake on Zn deficiency from parboiled rice is less than non-parboiled rice. Despite Zn losses during processing, biofortified rice could provide over 50% of the Zn EAR for children.